An Analysis Of English Jargon Used In Hand Phone - Hidayat, Muchlis (2005)
The research is aimed at giving a description on how English jargons are used in hand phone. This research is intended to help the students, the handphone users and the readers to understand the forms, the meaning and the function of English jargons. In conducting the research, the writer uses the qualitative research. The techniques of colecting the data are identifying the jargon, reading all the terms used in handphone, and make a list of the English jargons found in handphone. The writer first read all the term from the book, magazine, and the handphone itself. Then classifying the data that will be analyzed. In analyzing the form the writer uses morphological theory, to analysis meaning the writer uses semantics theory and to analyze function the writer uses Holmes' theory The result of this research shows that the forms of English jargon can be classified into two: word and phrase. Words are divided into six categories: word formation, derivation, compounding, acronym abbreviation, blends and back formation. Viewed from the meaning there are seven categories, they are: (1) the meaning of the jargon relate to message. (2) the meaning of the jargon relate to location. (3) The meaning of the jargon relates to accessory. (4) the meaning of jargon related to network. (5) The meanings of jargon related to way of calling (6) the meaning of jargon related to feature and (7) the meaning of jargon related to sound. The function of the jargon is to use the phone easily.